Peningkatan Literasi Artificial Intelligence dan Etika Digital bagi Siswa Madrasah Aliyah Al Syahni dalam Menghadapi Era Society 5.0 - Irwandi Rizki Putra; Muhlisahtun Niswah; Indrayani; Iriene Putri Mulyadi; Mesy Yulandari (Indra Institute Research & Publication, 2025)
This study aims to improve Artificial Intelligence (AI) literacy and digital ethics awareness among students at Madrasah Aliyah Al Syahni, Indragiri Hilir, in order to prepare them to face the dynamics of the Society 5.0 Era. The method used is Action Research with a participatory approach involving the cycle of planning, implementation, evaluation, and reflection. The research subjects consisted of students and teachers at Madrasah Aliyah Al Syahni, which currently still uses a manual data management system. Data collection instruments included a Likert scale questionnaire, in-depth interviews, and classroom observations. The results of the study showed a significant increase in students' AI literacy, especially in the cognitive (+36.7%) and affective (+38.7%) aspects, after the implementation of AI tools such as Socratic and ChatGPT. The findings also indicate that strengthening digital ethics based on Islamic values ​​and Maqasid al-Shari'ah is very effective in mitigating the risk of plagiarism and technology dependency. In conclusion, the integration of structured AI with a foundation of digital ethics can create an adaptive, responsive, and humanistic learning ecosystem in accordance with the vision of Society 5.0.